Penerapan Prinsip Kurikulum Merdeka dalam Pembelajaran Bahasa Arab - Al Kanza, Luthfia; Iswandi, Irvan; Fanirin, Moch. Hasyim (INCARE, International Journal of Educational Resources, 2024)
This journal examines the implementation of the Merdeka Curriculum principles in Arabic language learning in the 7th grade at Madrasah Tsanawiyah Ma’had Al-Zaytun Indramayu during the 2023/2024 academic year. The research problem focuses on the application of the Merdeka Curriculum principles in Arabic language learning in the 7th grade at Madrasah Tsanawiyah Ma’had Al-Zaytun Indramayu in the 2023/2024 academic year, as well as the evaluation of the curriculum's implementation in the same context. The purpose of this study is to assess both the application and the evaluation of the Merdeka Curriculum principles in Arabic language instruction in the 7th grade at the institution during the 2023/2024 academic year. This research employs a qualitative approach, utilizing observation and in-depth interviews with two Arabic language teachers of the 7th grade and 12 students as the sample for the 2023/2024 academic year. The results show that the application of the Merdeka Curriculum principles in Arabic language learning in the 7th grade at Madrasah Tsanawiyah Ma’had Al-Zaytun is aligned with the curriculum's core principles. The school has also integrated modern technology into the learning process, which is one of the key components of the Merdeka Curriculum. However, since the implementation is still in progress, the outcomes have not yet reached their full potential.